PENANGANAN STUNTING DENGAN PEMILIHAN PANGAN BERBASIS PANGAN LOKAL DI SD 2 KEBAYAKAN - Anna Permatasari Kamarudin; Amna Amna; Whin Themas Mico Saputra; Khadijah Khadijah; Ilma Fitri (Gapenas Publisher, 2023)
Stunting is a serious problem in this country. Stunting cases in Aceh reached 33.2%, which is above the national average of 22%. Although there have been many government programs run by puskesmas and posyandu, however stunting still exists in several villages, some of which are also not detected. Knowledge about stunting cases needs to be disseminated, both in terms of the problem, its characteristics, prevention and interventions that can be carried out by stakeholders. This community service was carried out on September 24, 2022 in the yard of SD 2, Kebayakan. This program aims to provide knowledge and understanding about stunting as well as provide skills to partners, namely parents of students and teachers at the school. The implementation of the dedication went well and smoothly. The results of the Pre Test and Post Test that were carried out showed that partners' knowledge and understanding of stunting cases had increased. There was an increase in knowledge as much 40%, from 56% to 96%. This activity shows that the prevention and prevention of stunting can be done by making a menu based on local foodstuffs with relatively cheap and easy-to-obtain protein content, such as chicken and tofu. The hope is that partners can process food with their own creativity so that their children, especially toddlers and under-fives, do not experience growth and development problems